Pengaruh Kegiatan Promosi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen Menggunakan Jasa Pengiriman Pada J&T Express Cabang Graha Raya Serpong Kota Tangerang Selatan - Ahmadi Muhaimin As; Fauziah Septiani (Jurnal Manajemen & Pendidikan [JUMANDIK], 2024)
Abstract. The aim of this research is to determine the influence of promotional activities and service quality on consumer purchasing decisions in using delivery services at the J&T Express Graha Raya Serpong Branch, South Tangerang City. The method used is quantitative. The sampling technique used the Slovin formula and a sample of 99 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that promotional activities have a significant effect on purchasing decisions, this is proven by hypothesis testing, obtained t count > t table or (9.543 > 1.985). Service quality has a significant effect on purchasing decisions, this is proven by hypothesis testing, obtained t count > t table or (8.824 > 1.985). Promotional activities and service quality simultaneously have a significant effect on purchasing decisions with the regression equation Y = 7.153 + 0.442X1 + 0.391X2. The correlation coefficient value is 0.787 or has a strong level of relationship with determination of 62.0% while the remaining 38.0% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (78.337 > 2.700).